Preclinical validations of [18F]FPyPEGCBT-c(RGDfK): a 18F-labelled RGD peptide prepared by ligation of 2-cyanobenzothiazole and 1,2-aminothiol to image angiogenesis - Didier J. Colin; James A. H. Inkster; Stéphane Germain; Yann Seimbille (SpringerOpen, 2016)
Abstract Background αVβ3, αVβ5 and α5β1 integrins are known to be involved in carcinogenesis and are overexpressed in many types of tumours compared to healthy tissues; thereby they have been selected as promising therapeutic targets. Positron emission tomography (PET) is providing a unique non-invasive screening assay to discriminate which patient is more prone to benefit from antiangiogenic therapies, and extensive research has been carried out to develop a clinical radiopharmaceutical that binds specifically to integrin receptors. We recently reported the synthesis of a new 18F-labelled RGD peptide prepared by 2-cyanobenzothiazole (CBT)/1,2-aminothiol conjugation. This study aims at characterising the preclinical biologic properties of this new tumour-targeting ligand, named [18F]FPyPEGCBT-c(RGDfK). The in vitro binding properties of [18F]FPyPEGCBT-c(RGDfK) were analysed by standard binding assay in U-87 MG and SKOV-3 cancer models and its selectivity towards integrins by siRNA depletions. Its preclinical potential was studied in mice bearing subcutaneous tumours by ex vivo biodistribution studies and in vivo microPET/CT imaging. Results In vitro, FPyPEGCBT-c(RGDfK) efficiently bound RGD-recognising integrins as compared to a control c(RGDfV) peptide (IC50 = 30.8 × 10−7 M vs. 6.0 × 10−7 M). [18F]FPyPEGCBT-c(RGDfK) cell uptake was mediated by an active transport through binding to αV, β3 and β5 but not to β1 subunits. In vivo, this new tracer demonstrated specific tumour uptake with %ID/g of 2.9 and 2.4 in U-87 MG and SKOV-3 tumours 1 h post injection. Tumour-to-muscle ratios of 4 were obtained 1 h after intravenous administration of the tracer allowing good visualisation of the tumours. However, unfavourable background accumulation and high hepatobiliary excretion were observed. Conclusion [18F]FPyPEGCBT-c(RGDfK) specifically detects tumours expressing RGD-recognising integrin receptors in preclinical studies. Further optimisation of this radioligand may yield candidates with improved imaging properties and would warrant the further use of this efficient labelling technique for alternative targeting vectors.